1996
DOI: 10.1159/000126931
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Gene Transcription of Adenohypophyseal Hormones in the Ovine Pars tuberalis

Abstract: Specific cells of the hypophyseal pars tuberalis (PT) have been associated with the transmission of photoperiodic stimuli to the endocrine system. However, their principal secretory products have not been identified yet. Therefore we studied the expression of several adenohypophyseal hormones and their subunits (TSH, FSH, LH, common α-chain, GH, ACTH, PRL, α- and γ-MSH, β-lipotropin) by immunocytochemistry, Northern blot analysis and in situ hybridization in the sheep pituitary. Only the common α-chain of glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Furthermore, it has been shown that in the hamster PT, the expression of β-TSH is regulated by the photoperiod [15,16]. In other mammals, such as sheep, mRNAs encoding for the 3 PD-glycoprotein hormones have been demonstrated in the PT, although only GSU and β-LH have been revealed by immunocytochemistry [17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that in the hamster PT, the expression of β-TSH is regulated by the photoperiod [15,16]. In other mammals, such as sheep, mRNAs encoding for the 3 PD-glycoprotein hormones have been demonstrated in the PT, although only GSU and β-LH have been revealed by immunocytochemistry [17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…The PT is mainly composed of secretory active PTspecific cells (11,12). PT-specific cells represent a distinct hypophyseal cell type that transcribes TSH␣ and -␤ in a considerable amount in all species investigated to date, but does not resemble thyrotropes of the pars distalis (PD) (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, expression of further necessary genes does not follow (Lanctot et al, 1999). These cells do not react with a specific antibody against the ␤-subunit of LH (Böckers et al, 1996;Stoeckel et al, 1994). The folliculostellate cells of the PT differ from those described in the PD (Kameda, 1996a(Kameda, , 1996b.…”
mentioning
confidence: 88%
“…The PT is a bi-or multilayered region formed by specific secretory cells (the so-called PT-specific cells), folliculostellate cells, and migratory cells coming from the PD (Oota and Kurosomi, 1966;Cameron and Foster, 1972;Stoeckel and Porte, 1984). The diameter of the secretory granules differs according to the species (Dellman et al, 1974) The presence in the PT caudal zone of hormones produced in the PD, particularly LH, FSH, and TSH, has been demonstrated in some species by immunocytochemical techniques (Baker and Yu, 1975;Girod et al, 1980;Asa et al, 1983;Gross, 1984;Böckers et al, 1996). These endocrine products are considered to be synthesized by migratory cells coming from the PD.…”
mentioning
confidence: 99%